Human CD19-specific switchable CAR T-cells are efficacious as constitutively active CAR T-cells but cause less morbidity in a mouse model of human CD19+ malignancy. Issue 12 (15th December 2022) - Pennell, Christopher A; Campbell, Heather; Storlie, Meghan D; Bolivar-Wagers, Sara; Osborn, Mark J; Refaeli, Yosef; Jensen, Michael; Viaud, Sophie; Young, Travis S; Blazar, Bruce R
Abstract : Current Food and Drug Administration (FDA)-approved CD19-specific chimeric antigen receptor (CAR) T-cell therapies for B-cell malignancies are constitutively active and while efficacious, can cause morbidity and mortality. Their toxicities might be reduced if CAR T-cell activity was regulatable rather than constitutive. To test this, we compared the efficacies and morbidities of constitutively active (conventional) and regulatable (switchable) CAR (sCAR) T-cells specific for human CD19 (huCD19) in an immune-competent huCD19 + transgenic mouse model. Conventional CAR (CAR19) and sCAR T-cells were generated by retrovirally transducing C57BL/6 (B6) congenic T-cells with constructs encoding antibody-derived single chain Fv (sFv) fragments specific for huCD19 or a peptide neoepitope (PNE), respectively. Transduced T-cells were adoptively transferred into huCD19 transgenic hemizygous ( huCD19 Tg/0 ) B6 mice; healthy B-cells in these mice expressed huCD19 Tg . Prior to transfer, recipients were treated with a lymphodepleting dose of cyclophosphamide to enhance T-cell engraftment. In tumor therapy experiments, CAR19 or sCAR T-cells were adoptively transferred into huCD19 Tg/0 mice bearing a syngeneic B-cell lymphoma engineered to express huCD19. To regulate sCAR T cell function, a switch protein was generated that contained the sCAR-specific PNE genetically fused to an anti-huCD19 Fab fragment. Recipients of sCAR T-cells were injected with the switch to link sCAR effector with huCD19 + target cells. Mice were monitored for survival, tumor burden (where appropriate), morbidity (as measured by weight loss and clinical scores), and peripheral blood lymphocyte frequency. CAR19 and sCAR T-cells functioned comparably regarding in vivo expansion and B-cell depletion. However, sCAR T-cells were better tolerated as evidenced by the recipients' enhanced survival, reduced weight loss, and improved clinical scores. Discontinuing switch administration allowed healthy B-cell frequencies to return to pretreatment levels. In our mouse model, sCAR T-cells killed huCD19 + healthy and malignant B-cells and were better tolerated than CAR19 cells. Our data suggest sCAR might be clinically superior to the current FDA-approved therapies for B-cell lymphomas due to the reduced acute and chronic morbidities and mortality, lower incidence and severity of side effects, and B-cell reconstitution on cessation of switch administration.